Revolution and Resistance : Moral Revolution, Military Might, and the End of Empire - Tucker, David, 1951- (Book collections on Project MUSE., 2016)
"What will future wars look like? Will war with terrorists dominate our future? With the proliferation of insurgent activity around the globe, do we need to wage war in a "new" way? David Tucker disputes the suggestion that there is something new in today's warfare. He argues instead that the future of war is evident in its own history--a history as old as Caesar's campaigns against the Gauls or Native American insurgencies against the US Army--a history which at its most fundamental level is the story of resistance to power. To glean information about the future of war, Tucker examines its past, proposing an alternative military history to guide our armed forces' efforts. Conventional military history emphasizes great battles between regular armies, but Tucker believes that the cumulative effect of irregular warfare--terrorism, guerrilla warfare, insurgency--is historically as significant as the effect of the great battles. In six succinct chapters, he creates a new framework to explain the historical significance of changing patterns of conflict. This framework will encourage new considerations of conflict, the role of technology, and the importance of organization. The book will appeal to instructors of upper-division and graduate courses in national and homeland security studies, international studies, foreign policy studies, and history. Reader Patrick Garrity believes Tucker is tackling a "critical yet still intellectually undeveloped field of study" and that his book will appeal to both academic and general audiences."--Provided by publisher.